Environmental, Social, and Governance (ESG), Intellectual Capital and Firm Value: The Mediating Role of Competitive Advantage in Asia - Meilanda, Putri; Fuadah, Luk Luk; Mukhtaruddin, Mukhtaruddin (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study examines the role of Environmental, Social, and Governance (ESG) and Intellectual Capital (IC) in enhancing firm value, with competitive advantage as a mediating variable. This study employed a quantitative approach by analyzing secondary data from 882 Asian companies, consisting of 7,938 firm year observations covering the period 2015–2023, using Structural Equation Modeling (SEM) with SmartPLS 3. The findings show that ESG does not significantly affect firm value or competitive advantage. In contrast, IC has a positive effect on both competitive advantage and firm value. Competitive advantage itself positively influences firm value and mediates the relationship between IC and firm value, but not between ESG and firm value. These results suggest that firm value improvement in Asia is more effectively driven by optimizing intellectual capital. Managers are encouraged to strengthen intellectual assets, ensure efficient financing, and improve the quality and integration of ESG practices to enhance competitiveness and long-term firm value.